THE ROLE OF PHYSICAL FITNESS TO IMPROVE THE SELF-QUALITY OF ELEMENTARY SCHOOL STUDENTS IN THE DISTRICT OF ACEH BESAR - Mansur, Mansur; K.S, Soegianto (The Journal of Educational Development, 2017)
This study is entitled "The Role of Physical Fitness to Improve the Self Quality of Elementary School Students in the district of Aceh Besar." The objective of this research is to describe the role of physical fitness in a self quality improvement of Elementary School students in the district of Aceh Besar. The population was the elementary school students in the district of Aceh Besar. The samples numbered 90 students were drawn from four, i.e. 60 from superior schools and 30 from the ordinary schools in the district of Aceh Besar. The method used in this research was descriptive quantitative. The data which were collected using a questionnaire (Likerâs scale) were analyzed using simple statistics. From the results of the data analysis, it was found that the responses of the students from the elementary schools in Aceh Besar district on the role of physical fitness in self improvement were as follows. (1) Strongly agree (63%), (2) agree (19%), disagree (10%) strongly disagree (8%). The implication of the results is that it is necessary to maximally apply learning activities that can enhance physical fitness so that the physical education teachers should actively contribute quantitatively and qualitatively to the optimum enhancement. The students who have a good understanding of the importance of physical fitness in various ways will feel the practical implementation of the learning activities conducted by physical education, sports, and health (penjasorkes) teachers both in curricular and extracurricular sessions. Physical education, sports, and health teachers should be able to design learning devices with teaching strategies that can stimulate the development and growth of the studentsâ psychomotor, cognitive, and affective aspects. Physical education, sports, and health learning can improve the students physical fitness and prevent them from various diseases such as obesity, heart disease, hypertension, and so on. Having a good physical fitness will also prevent them from insomnia and fatigue, and increase metabolism, intelligence, and health in attending the learning process at school. All parties should prioritize the improvement of the Elementary School studentsâ physical fitness in Aceh Besar district. Physical education, sports, and health teachers are suggested to increase the resources in order to implement the learning process using reliable competencies which are appropriate to the growth and development of low-grade elementary school students.